Effect of the Reproduction Method in an Artificial Selection Experiment at the Community Level - Raynaud, Tiffany; Devers, Marion; Spor, Aymé; Blouin, Manuel (Frontiers in Ecology and Evolution, 2019)
Selection at the group level is proposed to be an evolutionary process occurring in the context of multilevel selection in natura. In artificial selection experiments, selecting at the community level can allow to find multispecies assemblages that are more efficient than a single species at solving a given problem. In such procedures, the main difficulty is to find a balance between variation and heritability, which are both essential for selection to act. The aim of our study was to determine if the way of creating offspring units of selection from parental units, called “reproduction method”, could influence artificial selection efficiency through a differential in the variation/heritability balance. Selecting microbial communities depending on their biomass production and propagating them either one by one or in a mix of three communities, we showed that there were only transient phases of divergence between the two reproduction methods with a loss of the effect of artificial selection on community phenotype at certain cycles and a low heritability. However, mixing parental communities was more efficient at increasing biomass production than using a single parental community (+5% of biomass). We discussed the role of differences in community richness and structure in explaining these results.